x(x-y)+y(x+y)=

Simple and best practice solution for x(x-y)+y(x+y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-y)+y(x+y)= equation:


Simplifying
x(x + -1y) + y(x + y) = 0
(x * x + -1y * x) + y(x + y) = 0

Reorder the terms:
(-1xy + x2) + y(x + y) = 0
(-1xy + x2) + y(x + y) = 0
-1xy + x2 + (x * y + y * y) = 0
-1xy + x2 + (xy + y2) = 0

Reorder the terms:
-1xy + xy + x2 + y2 = 0

Combine like terms: -1xy + xy = 0
0 + x2 + y2 = 0
x2 + y2 = 0

Solving
x2 + y2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1y2' to each side of the equation.
x2 + y2 + -1y2 = 0 + -1y2

Combine like terms: y2 + -1y2 = 0
x2 + 0 = 0 + -1y2
x2 = 0 + -1y2
Remove the zero:
x2 = -1y2

Simplifying
x2 = -1y2

Combine like terms: -1y2 + y2 = 0
x2 + y2 = 0

The solution to this equation could not be determined.

See similar equations:

| (5t-2)t=3 | | 5.76-4.24x-1.9=27.864 | | 1+7-16=x | | X^2-x-380=0 | | 12x^2*42-4=8 | | -10x-5=0 | | y-4=-5 | | 2x-3(x-5)=6 | | x/y=2/7 | | -18x+14x=14x-18 | | x/8+x/7=x/9 | | 30+4-7=x+7 | | -2.1(z+0.9)=2.1(z+1.6) | | 3(m+1.5)=1.5(sm+3) | | 8m+56=12m+80 | | 7x-17=-3x-7 | | 3(4c-2)-4=8c+6 | | 3/4h=2-1/2h | | x^4-2x^3-35=0 | | 16+4^3*2/16 | | 4x+26=-x+6 | | 6x*2=15-x | | 6x-60=-5x-5 | | 0.6v+2.1=4.4 | | 150m+2500=3000+125m | | x+8=8x+8 | | 3x-16+12=3x+6-2x+3 | | 1/3+2/3m=-2/3 | | 1+f/2=4 | | 10x-100-70= | | x-8/8=x/16 | | n=m+z |

Equations solver categories